Immune thrombocytopaenia in children and adolescents - current management and Polish perspective - Marta Andrzejewska; Ewelina Truszkowska; Katarzyna Derwich (Termedia Publishing House, 2024)
Immune thrombocytopaenia (ITP) is the most common cause of acquired thrombocytopaenia diagnosed in paediatric patients. It is described as an isolated thrombocytopaenia without other factors, which may cause a decrease in platelets. Therefore, the diagnosis is of exclusion. Over the last few years, its management has significantly developed, and a paradigm switch in second-line treatment is being observed. Currently, thrombopoietin receptor agonists (TPO-RA) are available in Poland, which reduce the need for splenectomy in affected patients. The use of thrombopoietin receptor agonists has also provoked a change in definitions, especially concerning refractory ITP. This review focuses on an overview of currently recommended diagnostics and treatment of ITP, ongoing research concerning genetic predisposition, the use of TPO-RA, other immunosuppressive agents, and the role of splenectomy. We summarise congenital thrombocytopaenic disorders, which are the most often mistaken as ITP and need to be considered in the differential diagnosis.